The Moderating Role of Government and the Mediating Role of Commitment in the Relationship between Shared Leadership and Organizational Performance in Jakarta - Putri Allana, Abdullah (2024)
The purpose of the study was to investigate the influence of sharedleadership on company performance with the role of government as a moderation variable and organizational commitment as a mediation variable. The location of the research at the Tourism and Creative Economy Office of DKI Jakarta Province, Indonesia. The research design is a case study with non-parametric quantitative methods. Research sampling techniques are simple random sampling, a sample of 105 respondents, and hypothesis testing using the SMART-PLS software tool. The findings consist of five subdiscussions. First, sharedleadership is able to significantly improve organizational performance through seven indicators. Second, sharedleadership through the most dominant indicator, namely establishing teamwork, has a positive effect in increasing organizational commitment. Third, organizational commitment is proven to improve organizational performance. Fourth, the role of the government through its five indicators is proven to improve organizational performance well. Fifth, the role of government has not been able to strengthen the relationship of sharedleadership to organizational performance. Further findings, sharedleadership and organizational commitment are able to contribute to improving the performance of employees of the Tourism and Creative Economy Office of DKI Jakarta Province, Indonesia. However, the government's role is still weak in supporting implementation in the field. Because of technical constraints where employees do not understand their main duties professionally. In order to improve performance, the commitment of each level of the scope of the DKI Jakarta Provincial Tourism and Creative Economy Office is highly expected. Thus, it is important for the DKI Jakarta Provincial Tourism and Creative Economy Office to prioritize the planning aspects of Regional Apparatus along with control and evaluation functions. And adequate operational budget support and leadership oriented to togetherness / share so that the tourism activity program is sustainable.